How and when is social networking important? Comparing European expatriate adjustment in China and Turkey - (:unkn) unknown (My University, 2006)
Social interaction has been demonstrated to be a main predictor of expatriate adjustment. However, the impact of social interaction on expatriate adjustment may vary for those in different cultures. Contextual factors, such as geographic proximity and cultural differences between the home country and the host country, may have a significant impact on the expatriate adjustment process. The current paper singles out the above contextual factors by comparing European expatriates in China and in Turkey. European expatriates in China (n = 61) and Turkey (n = 69) were surveyed to explore the different patterns of social interactions (personal network and support), and the impact of these on the psychological well-being of the two groups. The empirical evidence gathered by the current study will delineate these differences and similarities and their impacts on the expatriates' psychological well-being in these two host countries. Crown Copyright © 2006.